2010
DOI: 10.1088/0957-0233/21/5/054017
|View full text |Cite
|
Sign up to set email alerts
|

Novosibirsk terahertz free electron laser: instrumentation development and experimental achievements

Abstract: Nowadays, the Novosibirsk free electron laser (NovoFEL) is the most intense radiation source in the terahertz spectral range. It operates in the continuous mode with a pulse repetition rate of up to 11.2 MHz (5.6 MHz in the standard mode) and an average power of up to 500 W. The radiation wavelength can be precisely tuned from 120 to 240 mm with a relative line width of 0.3-1%, which corresponds to the Fourier transform limit for a micropulse length of 40-100 ps. The laser radiation is plane-polarized and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(51 citation statements)
references
References 59 publications
(67 reference statements)
0
51
0
Order By: Relevance
“…We measured transparency of a few AO materials in the THz region of spectrum in a preliminary experiment carried out by means of the Novosibirsk free-electron laser (FEL) [4]. It was found that the majority of known AO-materials were opaque.…”
Section: Resultsmentioning
confidence: 99%
“…We measured transparency of a few AO materials in the THz region of spectrum in a preliminary experiment carried out by means of the Novosibirsk free-electron laser (FEL) [4]. It was found that the majority of known AO-materials were opaque.…”
Section: Resultsmentioning
confidence: 99%
“…A free electron laser 3 reported by the Institute of Nuclear Physics (Novosibirsk, Russia) generates an average power of 0.5 kW; however, it is as large as a building, housed in a large high bay facility. In addition to that, a gyrotron with pulsed magnetic field operating in a single 50 µs pulse with output power 1.5 kW 4 has been reported by the Institute of Applied Physics (Nizhny Novgorod, Russia).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to that, a gyrotron with pulsed magnetic field operating in a single 50 µs pulse with output power 1.5 kW 4 has been reported by the Institute of Applied Physics (Nizhny Novgorod, Russia). This gyrotron requires a cryomagnet and a diamond window, and including its power supply is about 2m 3 in volume and not portable.…”
Section: Introductionmentioning
confidence: 99%
“…Linac driven FELs use each electron pulse once, leading to low duty cycles. (Energy recovery linacs reach high duty cycles by recovering the electron energy [36,37,38].) Storage rings, by contrast, naturally operate at MHz repetition rates (determined by the revolution time of the electrons), and fully filled rings can provide CW radiation.…”
Section: Introductionmentioning
confidence: 99%